Development of the impact of tinnitus in children questionnaire (iTICQ) - Smith, Harriet; Fackrell, Kathryn; Kennedy, Veronica; Barry, Johanna G.; Benton, Claire; Partridge, Lucy; Hoare, Derek J. (Frontiers in Audiology and Otology, 2024)
Introduction: Tinnitus is a common disorder of the auditory system. Questionnaires are essential tools for clinical assessment and research. Whilst many questionnaires are available to measure different aspects of tinnitus complaint in adults, there is currently no self-report questionnaire measure of tinnitus that has been developed for or is suitable for use with children. This study describes the development of the first self-report measure of tinnitus impact for children aged 8 to 16 years old. Methods: Two phases of questionnaire development were conducted. In Phase 1 children's tinnitus-related problems were elicited from interviews with children with tinnitus (n=11; aged 9-16 years old), parents (n=5), and clinicians (n=8). Interview transcripts were analysed using qualitative content analysis. Findings were combined with problems identified by the clinical coauthors, researchers, and clinicians in a conference workshop, and those previously reported in service evaluation of UK National Health Service paediatric tinnitus services and in a scoping review. From this, a conceptual framework of tinnitus impact on health-related quality of life in children was developed. Based on the conceptual framework, a 38-item pilot questionnaire was drafted. In Phase 2, content validity of the pilot questionnaire was assessed in cognitive interviews with six children who had tinnitus (aged 8-15 years old) and an online survey with clinicians working in paediatric tinnitus services (n=8 services and 28 clinicians). Finally, readability assessments were conducted. Feedback led to iterative revisions to the questionnaire. The final questionnaire was named the Impact of Tinnitus in Children Questionnaire (iTICQ) Results: The iTICQ contains three scene setting (non-scoring) items, and 33 scoring items covering six domains of tinnitus impact: Sleep and Feeling Tired, Learning, Emotional Health, Hearing and Listening, Taking Part, and Relationships. Conclusions: The iTICQ is a new self-report measure of tinnitus impact that can be self-completed by children aged 8-16 years old. It shows good content validity and can be used to measure problem severity across the domains of core relevance to children with tinnitus. Further